Desenvolvimento de um software para o estudo da dispersão tridimensional transiente de poluentes em aquíferos utilizando fluidodinâmica computacional (CFD) - Silva, André Luiz da (2024)
The growing concern about groundwater contamination due to human activities requires the development of models capable of predicting the dispersion of pollutants in these environments. This work addresses the mathematical modeling and numerical simulation of the three-dimensional and transient propagation of pollutants in aquifers, focusing on the mechanisms of transport and transformation of contaminants. A mathematical model was implemented using the finite volume method for the discretization of the conservation equations and a computational model with a graphical interface was developed. The research included mesh convergence analysis and model sensitivity to assess stability and accuracy, comparing the results with the existing literature. Realistic scenarios of benzene and xylene leakage in sandy and sedimentary aquifers were simulated under different boundary conditions, reflecting situations of fuel tank leakage. The results indicated that benzene presents greater mobility compared to xylene in all situations analyzed. Furthermore, the pollutant plume reaches a greater range in sandy aquifers, while in sedimentary aquifers the propagation is more limited and subject to variations due to lithological heterogeneities. The graphical interface developed facilitated data entry and visualization of results, making the model accessible to a wide range of users, including non-specialists. This study culminates in a robust scientific tool capable of simulating realistic scenarios of hydrocarbon contamination in different types of aquifers, providing a detailed analysis of the processes involved and contributing to the advancement of environmental sciences.